Perioperative outcomes and complication rates in holmium laser enucleation of the prostate patients after prior prostate biopsy: does it really make a difference? A propensity score matched analysis - Hartung, Friedrich; Egen, Luisa; Grüne, Britta; Netsch, Christopher; Patroi, Paul; Kriegmair, Maximilian; Hardenberg, Jost von; Rassweiler-Seyfried, Marie-Claire; Michel, Maurice Stephan; Wenk, Maren; Herrmann, Jonas (Journal of endourology, 2024)
Introduction: Before holmium laser enucleation of the prostate (HoLEP), many patients have undergone short-term prostate biopsy (PB) to rule out the presence of prostate cancer. The aim of this study is to determine whether a short-term PB before HoLEP has an impact on the perioperative outcomes or complications of HoLEP. - Methods: In total, 734 consecutive patients treated with HoLEP at a tertiary care university hospital between January 2021 and July 2023 were retrospectively enrolled. Patients who had PB within 6 months before HoLEP were matched to patients who underwent PB more than 6 months or had no PB before HoLEP using propensity score matching (PSM) based on age, prostate volume (PV), prostate-specific antigen (PSA), preoperative urinary tract infection (UTI), and surgeon. Perioperative parameters, such as operation time (OT), enucleation efficiency (EF), as well as complications according to the Satava classification, the Clavien-Dindo classification (CDC), and the Comprehensive Complication Index (CCI) were evaluated. - Results: In total, 206 patients were matched. Age, PV, PSA, as well as the presence of a preoperative UTI and surgeons did not differ significantly between both groups after PSM. There were no significant differences in mean OT (75 vs. 81 minutes, p = 0.28) and EF (2.13 vs. 2.13 g/min, p = 0.99). No differences were noted regarding intraoperative (16 vs. 25, p = 0.16) or postoperative complications graded by CDC (p = 0.53) and CCI (p = 0.92). - Conclusion: PB within 6 months preoperatively before HoLEP showed no effect on perioperative outcomes or intra- and postoperative complications.